2013
DOI: 10.3350/cmh.2013.19.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors that influence the survival rates in liver cirrhosis patients with spontaneous bacterial peritonitis

Abstract: Background/AimsSpontaneous bacterial peritonitis (SBP) has been known to greatly influence the survival rate of patients with liver cirrhosis. However, the factors that affect the survival rate in patients with SBP need to be clarified.MethodsThis study enrolled 95 liver cirrhosis patients diagnosed with SBP. The laboratory findings of their serum and ascitic fluid were examined and the characteristics of the isolated microorganisms in their peritoneal fluid were analyzed.ResultsThe proportion of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
46
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 22 publications
13
46
1
1
Order By: Relevance
“…The multivariate analysis showed that serum urea, blood leucocyte count, Child–Pugh score and mean arterial pressure were independent predictive factors of mortality. These findings are consistent with previous studies and highlight the importance of liver and renal function, sepsis severity, and haemodynamic impairment in the prognosis of SBP.…”
Section: Discussionsupporting
confidence: 93%
“…The multivariate analysis showed that serum urea, blood leucocyte count, Child–Pugh score and mean arterial pressure were independent predictive factors of mortality. These findings are consistent with previous studies and highlight the importance of liver and renal function, sepsis severity, and haemodynamic impairment in the prognosis of SBP.…”
Section: Discussionsupporting
confidence: 93%
“…33 In a study by Tsung PC et al Eschericia coli (12 of the 47 cases, 25.5%), Klebsiella species (9 cases, 19.1%) and Streptococcus species (9 cases, 19.1%) were the most common organisms in this study, Enterococcus species (6 cases, 12.8%). 34 In our study the types of cultured bacterial organisms did not affect the survival rates of cirrhotic patients with SBP.…”
Section: Discussionmentioning
confidence: 41%
“…1 Spontaneous bacterial peritonitis is a complication that is life threatening and seen in cirrhotic progress. According to the literature, 8% to 27% of patients admitted with ascites to a hospital have SBP.…”
Section: Discussionmentioning
confidence: 99%
“…1 No valid parameters to predict SBP-related mortality have been identified. 2 However, if not treated, SBP can be fatal in 50% of patients and serious complications may arise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation